The Influence Of Organizational Communication On The Effectiveness Of Work Team In The Medan City Social Services Department - Ketaren, Meiske Davina Br; Butar-butar, Freddy (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine The Influence of Organizational Communication on the Effectiveness of Work Teams in the Medan City Social Service. This study involved active employees in the Medan City Social Service. PSI (Information System Center) provided a total of 115 participants for this study. Medan City Social Service 2024, where 44 Permanent Employees and 71 Casual Daily Employees (PHL) . The value of the coefficient of determination (R Square) and the influence of organizational communication based on the results of the regression analysis, the value of the coefficient of determination (R Square) is 0.816, which means that organizational communication is able to explain 81.6% of the variation in the effectiveness of work teams in the Medan City Social Service. This shows that organizational communication has a very strong and significant influence on the effectiveness of work teams. In other words, the better organizational communication that occurs in the work environment, the effectiveness of teamwork will also increase significantly. The remaining 18.4% of work team effectiveness is influenced by other factors outside of organizational communication. Majority of Respondents The majority of respondents in this study were employees aged between 25–32 years (56.5%), who are included in the productive age group. In terms of organizational communication, 66.1% of respondents rated organizational communication in their workplace as high, and 67% of respondents rated the effectiveness of work teams as high. This indicates that the majority of employees have a positive perception of communication and team effectiveness in their work environment, although there are still a small number who experience obstacles in the division of tasks, workload, and suboptimal two-way communication.